AN ASSEMBLED SKETCH OF PLACE NAMES IN LAC DUONG DISTRICT, LAM DONG PROVINCE - Thi Thuy Dung Vo; Thanh Hoai Nguyen; Thi Thanh Dam Le (Tạp chí Khoa học Đại học Đà Lạt)
Lac Duong District, located in Lam Dong Province, is traditionally inhabited by the Cơ Ho people (also known as the K’Ho), who are divided into two major subgroups: Chil and Lạch. The district is noted for its unique cultural and historical features, partly reflected in its place names. This study, conducted over a year in 2023, involved selecting and analyzing names of places in Lac Duong District by qualitative methods, statistical analysis, linguistic analysis, and place-name grouping. The paper classifies these names into four groups and examines the characteristics of Lac Duong District in terms of etymology, cultural space, historical period, and cultural subject. The findings provide a concise, yet significant, insight into the district’s cultural and historical depth. In the context of increasing cultural and economic exchanges, this research is timely and essential for supporting the preservation and promotion of the local residents’ cultural identity.